Economic Losses Estimation due to Rejection of Indonesian Exported Food - Winiati P Rahayu; Citra Prasetyawati; Yuanita Arizona; Wibisono Adhi (Institut Transportasi dan Logistik Trisakti, 2020)
Export rejection has become an issue of concern for both exporting and importing countries. Rejection of food exports that occur directly or indirectly resulted in losses experienced by many parties. The purposes of this research were to identify the factors that play a role in the calculation of the estimated economic losses due to the rejection of export food and estimated the value of the economic losses. The commodities studied were tuna, shrimp, and nutmeg. While the export destination studied were the United States, the European Union, and Japan. The method used in this research was survey and descriptive analysis. The calculation of the estimated economic losses was done by using the equation obtained from the result of a literature study and data collection. Components that contribute to the calculation of estimated losses due to a rejection of Indonesian exports consist of the loss of sales and related activities on communication, testing and retesting, transportation and execution. The highest economic losses based on data from the three years (2014-2016) was on tuna that was estimated at US3.01 million per year by the rejection from the United States. The transportation cost contributed to the highest loses as much as 59% or US2.4 million per year.